Thermal annealing effects on microstructure and mechanical properties of the Ta-W-Ta solid phase joints for neutron producing targets of the research nuclear facility “Source of Neutrons” - Lopata, A.A.; Domnich, M.P.; Borts, B.V.; Zelinsky, A.Yu.; Parkhomenko, A.A.; Sytin, V.I.; Tkachenko, V.I.; Vorobyov, I.A.; Pidlisnyi, A.D.; Patochkin, I.V.; Gluschenko, L.I. (Вопросы атомной науки и техники, 2022)
The paper considers the neutron-producing tantalum-tungsten-tantalum target using a niobium interlayer manu-facturing variant by means of vacuum hot roll bonding for the research nuclear facility “Source of Neutrons”. The metallography results and the Ta-W-Ta solid-phase junction specimens mechanical testing ones obtained by hot roll bonding in vacuum, both immediately after production and after the heat treatment in the temperature range of 900…1300°C after roll bonding, are presented. The influence of thermal annealing on the interaction nature of the clad layers with each other and with the core tungsten material of the Ta-W-Ta solid-phase junctions with Nb inter-layers obtained by vacuum hot roll bonding has been studied. Розглянуто варіант виготовлення нейтроноутворюючої мішені тантал-вольфрам-тантал з використанням прошарку ніобію методом гарячої вакуумної прокатки стосовно дослідницької ядерної установки «Джерело нейтронів». Представлені результати металографії та механічних випробувань зразків твердофазних з’єднань Ta-W-Ta, отриманих гарячою прокаткою у вакуумі як безпосередньо після отримання, так і термооброблених у діапазоні температур 900…1300°C після прокатки. Вивчено вплив температурного відпалювання на характер взаємодії плакованих шарів між собою та з матеріалом вольфрамового сердечника у твердофазних з’єднаннях Ta-W-Ta з прошарками Nb, які отримані методом гарячої прокатки у вакуумі. Рассмотрен вариант изготовления нейтронообразующей мишени тантал-вольфрам-тантал с использованием прослойки ниобия методом горячей вакуумной прокатки применительно для исследовательской ядерной установки «Источник нейтронов». Представлены результаты металлографии и механических испытаний образцов твердофазных соединений Ta-W-Ta, полученных горячей прокаткой в вакууме как непосредственно после получения, так и термообработанных в диапазоне температур 900…1300°C после прокатки. Изучено влияние температурного отжига на характер взаимодействия плакированных слоев между собой и с материалом вольфрамового сердечника в твердофазных соединениях Ta-W-Ta с прослойками Nb, полученных методом горячей прокатки в вакууме.